Factors Related to Student Compliance with the Smoke-Free Area Policy at SMK Negeri 1 Parigi Selatan - Muhammad Ryman Napirah; Vidyanto; Sri Rahmadani (Miracle Journal of Public Health, 2026)
Students can be unpredictable and sometimes do not comply with the No Smoking Area (NSA) policy. At SMK Negeri 1 Parigi Selatan, more than 50 students were found smoking in areas where the NSA has been implemented. This study aims to analyze the factors influencing student compliance with the NSA policy at SMK Negeri 1 Parigi Selatan. The study is quantitative in nature, taking the form of an analytical survey with a cross-sectional approach. The sample consisted of 125 male students selected using a total sampling technique. The data were analyzed using univariate and bivariate Chi-Square tests. The results showed significant relationships between student compliance with the NSA policy and attitudes (p = 0.001), facilities and infrastructure (p = 0.005), and peers (p = 0.009), with 95% confidence intervals (CIs) calculated using SPSS. It is expected that schools will organize education on the benefits of NSA to improve students' positive attitudes, provide educational posters in support of NSA, improve facilities and infrastructure, and hold workshops to enhance peer collaboration on the KTR policy.